Protective Effect of Fennel Oil on Cyclophosphamide Inhibited Spermatogenesis and Induced Oxidative Stress in Albino Rats. - Saber A.Sakr; Somaya Y. Shalaby; Rawan H. Beder (Journal of Biotechnology and Biomedical Science, 2017)
Introduction: Cyclophosphamide (CPA) is an anticancer drug .Fennel (Foeniculum vulgare Mill) essential oil is a traditional medicine used against many diseases. Aim. The present work studied the effect of fennel oil against testicular damage and oxidative stress induced by the anticancer drug, cyclophosphamide (CPA) in albino rats. Methods. Animals were divided into 4 groups: group1, control, group2, orally given fennel oil, group3 treated with CPA and group4 treated with CPA and fennel oil. The testes were removed for histological and immune histochemical preparation. Blood was collected and sera were prepared for hormonal and biochemical analysis. Results. The results revealed that CPA caused histological alterations in the testis including decrease in diameter and germinal epithelial height of the seminiferous tubules, degeneration of germ cells, cytoplasmic vacuolation and congestion of blood vessels. Cell proliferation marker was decreased and apoptotic marker caspase-3 was decreased. Biochemical results revealed decrease in the hormones LH and testosterone. Moreover, the serum activity of the antioxidant enzymes, SOD, CAT was decreased and the lipid peroxidation marker, DMA was increased. Treating rats with CPA and fennel oil caused an improvement in the histological structure of the testis. There was an increase in LH ,testosterone,SOD and CAT, while MDA level decreased. Conclusion. It is concluded that administration of fennel oil exhibited protective effects against CPA-induced reproductive toxicity in male rats. The protective effect of fennel oil might be due to induction of antioxidant defense systems by one or more of its constituents.
Keywords: Cyclophosphamide